Augmentation Effect of Low-Frequency Repetitive Transcranial Magnetic Stimulation Over Presupplementary Motor Area in Obsessive-Compulsive Disorder: A Randomized Controlled Trial - Arumugham, Shyam Sundar; Vs, Subhasini; Hn, Madhuri; B, Vinay; Ravi, Malvika; Sharma, Eesha; Thirthalli, Jagadisha; Reddy, Y C Janardhan (The journal of ECT, 2018)
The current study investigated the efficacy of low-frequency repetitive transcranial magnetic stimulation (rTMS) over bilateral presupplementary motor area (pre-SMA) in patients suffering from obsessive-compulsive disorder (OCD) with partial/poor response to pharmacotherapy, in a double-blinded randomized sham controlled trial. Forty subjects with OCD, who were on stable medications with partial/poor response to pharmacotherapy were randomly divided into 2 groups (n = 20 in each group), to receive either active or sham low-frequency rTMS over bilateral pre-SMA. Thirty-six patients were eligible for intent-to-treat analysis. There was no significant difference in relevant demographic and clinical variables between the 2 groups at baseline. There were no statistically significant differences between the 2 groups after 3 weeks of treatment in the Yale-Brown Obsessive Compulsive Scale score (time*group interaction, F2.48,84.16 = 0.80, P = 0.40) and other secondary outcome measures including responder rates and depressive and anxiety symptoms. Low-frequency rTMS over pre-SMA may not be effective as an augmenting agent in partial/poor responders to SRIs. This study underlines the need to explore alternate rTMS protocols in OCD.